Museum Art in Everyday Life - Corrine E. Glesne (LEARNing Landscapes, 2012)
Art museums engage diverse audiences in multiple forms of learning. Based on qualitative research at seven academic institutions, this article focuses on the role academic art museums play in the everyday life of students and faculty, on how people become interested in art and art museums, and on possible contributions of campus art museums beyond use in classes and research.